Design, construction and performance of the current lead test facility CuLTKa. (September 2017) - Richter, T.; Bobien, S.; Fietz, W.H.; Heiduk, M.; Heller, R.; Hollik, M.; Lange, C.; Lietzow, R.; Rohr, P.
Highlights: A cryogenic test facility for helium operation in forced-flow mode was built. Helium at 4.5 K and 20–70 K, simultaneously, can be provided. Test setup provides supply current up to 50 kA DC and withstand voltage of 50 kV DC. The cryogenic, electrical and process control setup is described in detail. Experiences during installation and commissioning are presented. Abstract: The Karlsruhe Institute of Technology (KIT) has a longtime experience in the development of High Temperature Superconductor (HTS) Current Leads (CLs) for high currents leading to several contracts with national and international partners. Within these contracts series production and cold acceptance tests of such CLs were required. The cold test of a large number of CLs requires the availability of a flexible facility which allows fast and reproducible testing. With theCu rrentL eadT est FacilityKa rlsruhe (CuLTKa) a versatile and flexible test bed for CLs was designed and constructed. The facility consists of five cryostats including two test boxes and is directly connected by a transfer line to a refrigerator with a capacity of 2 kW at 4.4 K. The refrigerator supplies supercritical helium at two different temperature levels simultaneously. Each of the two test cryostats can be equipped with a pair of CLs which is short-circuited at the low temperature level via a superconducting bus bar. For current tests a power supply can provide DC currents up to 30 kA. If required, the facility design offers the potential of withstanding high voltages of up to 50 kV on the test objects. The commissioning of the facility started in July 2014. In total a series of acceptance tests of the CLs for the Japanese JT-60SA will be carried out until second half of 2017 to qualify six CLs with a current of 26 kA and 20 CLs with a current of 20 kA. In the meantime, six CLs@26 kA and 16 CLs@20 kA have been tested in CuLTKa which demonstrates the very effective operation of the facility. This paper describes the setup of the facility from cryogenic, electrical and process control point of view and will highlight the design of particular technical aspects. Furthermore, an overview of the performance during the commissioning phase will be given.